Response of Seed Production and Pollen Viability in Cucumber (Cucumis sativus L.) to Potassium and Boron Fertilizer Application - Leli Kurniasari; Tamara Ferbrianika; Putri Santika (Journal of Applied Agricultural Science and Technology, 2026)
The improvement of cucumber cultivation practices, such as proper seed selection and appropriate fertilization, has the potential to enhance seed production and quality. Therefore, this study aimed to evaluate the most effective combination of potassium and boron fertilizer doses to improve seed production and pollen viability in cucumber. A randomized block design (RCBD) with two treatment factors was used. The first factor was potassium dose, applied at three levels: 100 kg/ha, 200 kg/ha, and 300 kg/ha. The second factor was boron dose, applied at four levels: 0 kg/ha, 1 kg/ha, 2 kg/ha, and 3 kg/ha. Data were analyzed using ANOVA, with a comprehensive set of observation parameters. In conclusion, no significant interaction was observed between potassium and boron treatments across all observed parameters. The treatment of 300 kg/ha potassium had a highly significant effect on the number of seeds per fruit (342.53), the number of filled seeds per fruit (289.93), seed weight per fruit (7.13 g), filled seed weight per fruit (8.24 g), and seed production per hectare (253.64 kg). Boron fertilizer treatment at a dose of 1 kg/ha had a highly significant effect on the time to emergence of male flowers (23.44 DAP), the time to emergence of female flowers (26.33 DAP), filled seed weight per fruit (7.86 g), and seed production per hectare (241.72 kg).